Non-muslim consumers attitude and repurchase behaviour towards halal food: an application of buyer behaviour model - Ag. Damit, Dayang Haryani Diana; Harun, Amran; Martin, David; Shamsudin, Abdul Shukor; Mohd Kassim, Abdul Wahid (UMS, 2018)
Halal food is widely recognised for its exceptional quality assurance and wholesomeness which attracts both Muslim and non-Muslim consumers. Previous studies have shed some light on the Muslim consumer attitude-behaviour interactions with halal products. However, studies of similar topic focusing on non-Muslim consumers as respondents are uncommon. Therefore, this study aims to examine the determinants of non-Muslim attitude and their repurchase intention on halal food product using the Buyer Behaviour Model. Data were collected through self-administered questionnaire survey involving 444 non-Muslim consumers. The structural equation analyses revealed that lifestyle, consumers past purchase experience, and religion adoption positively influenced the non-Muslim consumers’ attitude towards halal products. The findings also revealed a significant relationship between the attitude of non-Muslim consumer towards halal product and their repurchase intention of the halal product. Finally, several recommendations for future research consideration are presented in the final part of this paper.